Answer:
I can't answer this unless you give more information to the question.
Hi, there!
_____
To find the missing side length of this triangle (which is a <em>right</em> triangle), we'll use Pythagoras' Theorem.
![-\!\!\!-\!\!\!-\!\!\!\longrightarrow\boldsymbol{a^2+b^2=c^2}](https://tex.z-dn.net/?f=-%5C%21%5C%21%5C%21-%5C%21%5C%21%5C%21-%5C%21%5C%21%5C%21%5Clongrightarrow%5Cboldsymbol%7Ba%5E2%2Bb%5E2%3Dc%5E2%7D)
Here,
![\textsc{legs:}\begin{cases} \bold{a}\\\bold{b} \end{cases}](https://tex.z-dn.net/?f=%5Ctextsc%7Blegs%3A%7D%5Cbegin%7Bcases%7D%20%5Cbold%7Ba%7D%5C%5C%5Cbold%7Bb%7D%20%5Cend%7Bcases%7D)
Hypotenuse (the longest side): c
We know that
![\bold{a=2 \ and \ b=28}](https://tex.z-dn.net/?f=%5Cbold%7Ba%3D2%20%5C%20and%20%5C%20b%3D28%7D)
So, we can substitute our parameters, and solve for c.
square 2 and 28
add the numbers
square root both sides
![\bold{\sqrt{788}=c}](https://tex.z-dn.net/?f=%5Cbold%7B%5Csqrt%7B788%7D%3Dc%7D)
Hope the answer - and explanation - made sense,
happy studying!!
G (x) = x + 1 (fog) (x) = x 2 + 3x + 1 ⇒ (fog) (x) = x 2 + 3x + 1 ⇒ f (g (x)) = x 2 + 3x + 1 ⇒ f (x + 1) = x 2 + 3x + 1 Eg x + 1 = p, then x = p - 1. ⇒ f (p) = (p - 1) 2 + 3 ( p - 1) + 1 ⇒ f (p) = p 2 - 2p + 1 + 3p - 3 + 1 ⇒ f (p) = p 2 + p - 1 So f (x) = x 2 + x - 1 - ->
ANSWER IS : x 2 + x - 1
If you add the two terms on the right, you will get 5^14. 14 is your answer.
Answer: 27/3=9 which means 9$ per hour
32/4=8 which means 8$ per hour
Step-by-step explanation:
Answers is annie deal is the best